Public Perception of "Online Begging" Action on Tiktok Social Media - Sopiyani, Helen Fitri; Putri, Nabila Triananda; Nuruzzaman, H.M. (Asian Journal of Social and Humanities, 2025)
This study discusses the phenomenon of rampant online begging on social media, especially the TikTok platform. This phenomenon has emerged along with advances in information technology and ease of digital access that encourage individuals to take advantage of the live streaming feature to ask for gifts or donations from viewers. This study aims to analyze the causes, impacts, and public perceptions of this phenomenon. The method used is qualitative with data collection techniques in the form of observation, interviews, documentation, and data validation. The results of the study show that there are three main factors causing the rise of this phenomenon, namely advances in information technology, poverty problems, and the urge to seek sensation and popularity on social media. As a result, there has been a shift in social values in society that are more inclined towards instant ways of earning money, reduced social media ethics, and the emergence of inequality in perception in society towards this phenomenon. Public perceptions also vary, ranging from those who feel concerned, disturbed, to those who support as long as they do not harm other parties. These findings show the importance of a holistic approach through digital education, strengthening platform regulations, and attention to socio-economic factors that encourage online begging.